Efeito do treino de força e resistência na língua com o uso do Iowa Oral Performance Instrument na doença de Parkinson - Taucare, Exequiel del Carmen Plaza (2021)
Parkinson's disease is a progressive pathology of the motor system caused by poor dopamine production and is characterized by difficulty in coordination, potency, endurance and muscle control. Given the neuromotor nature of the disease, the oral phase of swallowing is affected, , in which multiple soft and bony structures act, including the tongue that plays an important role, both in the formation of the bolus and in the propulsion to the pharynx. Although numerous studies have focused their efforts on the analysis of the phenomenon of food transit, it is still necessary to deepen the knowledge in this area. Based on this premise, this study aimed to analyze the effects of a strength and resistance intervention program for the tongue in subjects with Parkinson's Disease. This research was approved by the Ethics Committee of the Federal University of Santa Maria and the Speech Therapy Clinic of the University of Talca, in Chile, where the collections were carried out. Two groups were formed with subjects with Parkinson's Disease. Both performed conventional tongue exercises and one with the addition of the Iowa Oral Performance Instrument during training. The electrical activity of the suprahyoid muscles and tongue pressure were pre-intervention, over 4 and 8 weeks of training, as well as in the 12th week, investigating detraining. Quality of life related to swallowing was measured before and after the intervention. It was found that all participants had lower tongue strength and endurance than those found in studies with healthy individuals. Subjects in more advanced stages of the disease had lower tongue strength. After the training, a significant increase in the electrical activity of the suprahyoid musculature and lingual strength was found in the group that performed the speech-language intervention associated with the Iowa Oral Performance Instrument compared to the control. Likewise the quality of life related to swallowing improved in the experimental group.